When the poor give more than the rich: The role of resource evaluability on relative giving. (17th June 2022) - Pittarello, Andrea; Motsenok, Marina; Dickert, Stephan; Ritov, Ilana
Abstract: Five experiments examined the role of resource evaluability on giving. We systematically varied participants' resources they and another potential donor received and whether they could donate to a recipient either by themselves or with the other donor. Participants in the relative advantage condition received more resources than the other donor, and those in the relative disadvantage condition received fewer resources than the other donor. The presence of the other donor made participants' resources evaluable and shaped giving: Relatively disadvantaged participants were proportionally more generous than advantaged participants but only when they could evaluate their resources. Neither the mere presence of others nor reputational concerns could explain the results. Exploratory mediation and moderation analyses further showed that relatively disadvantaged participants give proportionally more the higher and the more equal they perceive their status to the advantaged donor. This shows that the generosity of those who have less does depend on how they evaluate their status compared to other donors. Our results provide insights into the question of why and when resource asymmetries between donors result in prosocial giving and can influence fundraising strategies of charitable organizations.